Pengaruh Manajemen ASN dan Good Governance terhadap Kinerja Organisasi Perangkat Daerah Pada Kabupaten Pemekaran di Provinsi Bengkulu - Winda Tiara Rizki; Slamet - Widodo; Praningrum - - (Student Journal of Business and Management, 2021)
The aim of the research is to know the influence of ASN management and good governance on the Local Government performance at the Bengkulu Province. The primary data obtained through questionnaire to the apparatus at the Central Bengkulu Regency, Kepahiang Regency and Seluma Regency. The total sample used in the research is 319 respondents. The data analysis method is statistic descriptive and regression analysis. The result that: (1) the apparatus management have an influence on Local Government performance at the Bengkulu Province. It means that if the apparatus management is better, the Local Government Board performance is also getting better and (2) the public good governance has an influence on Local Government performance at the Bengkulu Province. It means that if the good governance is better, the Local Government performance is also getting better.